AB0671 Vitamine D Serum Level Correlates with Quadriceps Muscle Strength in Inflammatory Myositis. (9th June 2015) - Meyer, A.; Laverny, G.; Javier, R.-M.; Gottenberg, J.-E.; Geny, B.; Sibilia, J.
Abstract : Background: Vitamin D has been involved in both inflammation and muscle strength. Inflammatory myopathies are characterized by muscle inflammation and weakness. Objectives: We assessed whether vitamin D serum level is linked to muscle strength during inflammatory myopathies. Methods: Fourteen consecutive patients with inflammatory myopathies (with the exclusion of inclusion boy myositis) were prospectively included. Muscle strength was recorded on dominant quadriceps using hand held dynamometer. 25-OH-vitamin D3 level was measured on a blood sample at the same time. Results: Characteristic of the patients: 9 women and 5 men with a median age of 53.5 (13-71) were included. Duration of mysoitis at the time of muscle strength was 29 months (3-68). 11 patients were treated at the time of quadriceps strength measurements (corticosteroids n=11, methotrexate n=9, mycophenolate mofetil n=2, intraveinous immunoglobulin n=5). Vitamine D levels and quadriceps muscle strength: Median 25-OH-vitamine D3 level was 17.80μg/L (10.2-38.3) and median quadriceps strength (expressed as the percentage of the mean value recorded in healthy volunteers of the same age and sex) was 65% (14-107). 25-OH-vitamine D3 correlated with quadriceps muscle strength (figure : Spearman R =0.68, 95%CI: 0.22-0.89, p<0.01). Conclusions: Our data suggests that vitamin D is involved in muscle strength during inflammatory myopathies. 25-OH-vitamin D3 might be monitored in these patients not only with the aim of protecting bone during corticosteroids treatments but also with the objective of improving muscle strength. Disclosure of Interest: None declared